2023
DOI: 10.1007/s11227-023-05134-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultra-energy-efficient reversible designs of sequential logic quantum-dot cellular automata flip-flop circuits

Abstract: Quantum-dot cellular automata (QCA) is a technological approach to implement digital circuits with exceptionally high integration density, high switching frequency, and low energy dissipation. QCA circuits are a potential solution to the energy dissipation issues created by shrinking microprocessors with ultra-high integration densities. Current QCA circuit designs are irreversible, yet reversible circuits are known to increase energy efficiency. Thus, the development of reversible QCA circuits will further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The type and number of majority gates used to design a QCA circuit are critical aspects that can influence circuit specifications. In previous studies, only one type of majority gate, either the reversible majority gate [14,18] or the irreversible majority gate [32][33][34][35][36][37], was used in the design of QCA half-adder circuits. In terms of the number of majority gates used for designing the half-adder circuit, a few prior studies used five majority gates [34,36], whereas others used four majority gates 5 [14,18,37].…”
Section: Design Of Hybrid Qca Half-adder Circuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The type and number of majority gates used to design a QCA circuit are critical aspects that can influence circuit specifications. In previous studies, only one type of majority gate, either the reversible majority gate [14,18] or the irreversible majority gate [32][33][34][35][36][37], was used in the design of QCA half-adder circuits. In terms of the number of majority gates used for designing the half-adder circuit, a few prior studies used five majority gates [34,36], whereas others used four majority gates 5 [14,18,37].…”
Section: Design Of Hybrid Qca Half-adder Circuitsmentioning
confidence: 99%
“…In previous studies, only one type of majority gate, either the reversible majority gate [14,18] or the irreversible majority gate [32][33][34][35][36][37], was used in the design of QCA half-adder circuits. In terms of the number of majority gates used for designing the half-adder circuit, a few prior studies used five majority gates [34,36], whereas others used four majority gates 5 [14,18,37]. In this case study, we developed hybrid QCA half-adder circuits by simultaneously using three types of majority gates: reversible, irreversible, and partially reversible.…”
Section: Design Of Hybrid Qca Half-adder Circuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…With considerable advances in Nanoelectronics devices, Quantum-dot cell automata (QCA) is the most encouraging option in contrast to traditional CMOS innovation. QCA device has some advantages over other by high speed, high density, and low power consumption that are very helpful for the design of digital circuits 2 4 . This technology, without any transistor, is very helpful in designing circuits at the nanoscale level.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that combinational QCA circuits that are both logically and physically reversible can operate with energy dissipation values lower than Landauer's limit. Later, researchers implemented this technique to develop more sophisticated combinational QCA logic circuits, as well as sequential QCA circuits, characterized by feedback loops [21,22]. In this research, we introduce the first multilayer reversible QCA ALU built using the logically and physically reversible QCA design technique.…”
Section: Introductionmentioning
confidence: 99%